(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Knowledge of Ayurveda is based on specific fundamental principles. Dosha, Dhatu, Mala, Srotasa are some among them. Malas are the waste products which primarily generate after digestion of food. While Srotasa are the channels or pathways in the human body which carries Dosha, Dhatu, Mala and Mana. Sveda (sweat) is one of the waste product which forms after digestion of food or in the process of metabolism of adipose tissue. Formation, transportation and elimination of Sveda is carried out by Sveadavaha Srotasa and it helps to regulate body temperature, maintain skin moisture and excrete toxic substance from body. Detail description of concept Sveda, Svedavaha Srotasa, its normal mechanism, importance in manifestation of various diseases and its application in treatment is described in Ayurvedic texts. Thinking of this fact, for better acknowledgment of these concepts and its role in the practice this comprehensive review has been done.